Diversifikasi Produk Olahan Jamur Tiram untuk Menunjang Perekonomian Masyarakat di Kabupaten Jember - Muhammad Iwan Wahyudi; Bagus Tripama; Henik Prayuginingsih; Taufik Timur Warisaji (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
The Stimulus Community Partnership Program (SCPP) activities aims to support oyster mushroom farmers in Jember by improving skills and knowledge for diversifying oyster mushroom processing, building networks and markets, stimulating capital, and improving business managerial which are the main problems of partners in developing their businesses and economies. The SCPP activity method uses capacity building with a community driven development approach which is based on activities that are cognitive, affective, and psychomotor in the context of added value products and oyster mushroom business management including marketing to increase income and partner economy. The results of SCPP are in the form of improving partners' skills in processing oyster mushrooms into 5 prospective products that are needed by the market. In addition, increasing skills in business management starting from planning, organizing partne r members, evaluating product quality, simple bookkeeping, opening online/offline market access as well as strengthening capital in the procurement of production infrastructure are the next outputs of the service activities carried out. This program has been able to solve partner problems in improving the skills of diversifying oyster mushroom processing into processed products that have high prospects in the market. Improved business management and access to new markets, especially online, as well as injections of capital into fresh energy for partners and members to develop their businesses and economies.